PENGARUH VARIABEL SOSIO DEMOGRAFI DAN KARAKTERISTIK FINANSIAL TERHADAP SIKAP, NORMA SUBYEKTIF DAN KONTROL PERILAKU MENGGUNAKAN KARTU KREDIT (Studi Pada Pegawai di UKSW Salatiga) - Rita, Maria Rio; Kusumawati, Ratna (Jurnal Manajemen dan Keuangan, 2011)
Recent years have seen a boom in research on new electronic payment instruments. The purpose of this research is to investigate the influence of the socio-demographic variables and financial characteristics of attitude toward subjective norm and behavioral control to use credit cards on employees in Satya Wacana Christian University Salatiga. This study used a questionnaire as a tool to collect data, and techniques of analysis used is multiple regression analysis with dummy variables. The study shows that education levels (under graduate and doctoral program) affect the subjective norm and attitude using credit card. But socio-demographic variables and financial characteristics does not simultaneously affect the attitude, subjective norm and behavioral control using credit card.Keywords: Socio Demographic Variables, Financial Characteristics, Attitude, Subjective Norms, Control Behavior, Credit Cards